A green high-performance concrete pole mixed with recycled aggregate

Through the secondary treatment of wastewater in concrete mixing stations and the replacement of iron tailings powder, combined with the calcination of polymer aluminum chloride waste slag and calcium carbide slag, a high-performance concrete pole is formed, which solves the low bending strength and environmental pollution of concrete pole Problem, resource recycling and performance improvement have been achieved.

CN118851665BActive Publication Date: 2024-12-31GUANGDONG LONGJIANGYUAN CEMENT PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410879637.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2024-12-31
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

The existing concrete poles have low bending strength, high self-weight, and a large amount of wastewater is generated during the production process, resulting in environmental pollution, and excessive mining of river sand damages the ecosystem. It is necessary to find alternative ways to utilize recycled aggregates and wastewater to achieve environmental protection and performance improvement.

Method used

Polyaluminum chloride is used to treat the wastewater of the concrete mixing station secondary to remove suspended matter and impurities, and replace part of the river sand with iron tailings powder, and calcination is combined with the polymerized aluminum chloride waste slag and calcium carbide slag to form a high-performance concrete pole .

Benefits of technology

The resource recycling of wastewater and waste slag has been realized, production costs have been reduced, environmental pollution and garbage disposal pressure have been reduced, and the performance and environmental protection of concrete poles have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004924114280000062
    Figure BDA0004924114280000062
  • Figure BDA0004924114280000071
    Figure BDA0004924114280000071
  • Figure BDA0004924114280000081
    Figure BDA0004924114280000081
Patent Text Reader

Abstract

The invention discloses a green high-performance concrete pole mixed with recycled aggregate, belonging to the technical field of concrete. The pole is composed of green high-performance concrete mixed with recycled aggregate and a steel skeleton. The green high-performance concrete mixed with recycled aggregate includes 600-850 kg / m of cement in terms of mix ratio. 3 , silica fume 100~200kg / m 3 , fly ash 20~50kg / m 3 , Polyaluminium chloride waste residue 50~250kg / m 3 , Sand 800~1100kg / m 3 , Iron tailings powder 200~500kg / m 3 , carbide slag 10~50kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 8~15kg / m 3 , Fresh water 80~140kg / m 3 , Recycled water 30~60kg / m 3 The present invention also discloses a treatment process for wastewater from a concrete mixing station, which uses polyaluminium chloride to perform secondary treatment on the wastewater to obtain polyaluminium chloride waste residue and recycled water. The concrete pole of the present invention not only meets high requirements in terms of performance, but also realizes resource utilization of wastewater and waste residue obtained after treating the wastewater during the production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, and in particular to a green high-performance concrete pole mixed with recycled aggregates. Background Art

[0002] Concrete poles are the most widely used pole tower structure in the field of overhead lines in our country. Since ordinary concrete poles have weaknesses such as low bending strength and heavy weight, the service life of the poles is short and the maintenance workload is large. High-strength concrete is a new type of cement-based material with good mechanical properties and can be used in concrete pole structures.

[0003] However, in order to obtain better performance, high-strength concrete eliminates coarse aggregate and uses river sand with smaller particle size. Excessive exploitation of river sand will lead to a series of ecological problems such as riverbed decline, change in water flow velocity, riverbank erosion, etc., destroying the river ecosystem. Finally, a large amount of wastewater is inevitably produced in the production process of concrete. The wastewater from concrete mixing plants contains a variety of pollutants. If it is directly discharged without treatment, it will cause multiple hazards to the environment and ecosystem. At present, the treatment and reuse of wastewater from mixing plants have always been highly valued by industry practitioners. There are two commonly used solutions: one is to discharge clean water after the wastewater is settled and neutralized, and outsource the sediment to a garbage company for treatment. This method will not only occupy land, but also increase corporate expenditures and cause secondary pollution to the environment; the other solution is to filter the wastewater into mud cakes and then transport them for landfill, which has high treatment costs. Therefore, to achieve true environmental protection, zero pollution and zero emissions, it is necessary to find alternative recycled aggregates for river sand and find new ways to utilize wastewater while ensuring the performance of concrete. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention adopts polyaluminium chloride to carry out secondary treatment of wastewater from a concrete mixing station. The method can effectively remove suspended matter and impurities in the wastewater, reduce the pH value of the wastewater, and use iron tailings powder to replace part of the river sand, which not only reduces the proportion of river sand, but also enables the reuse of waste, reduces the amount of landfill, and alleviates the pressure of garbage disposal.

[0005] The technical solution to achieve the purpose of the present invention is as follows: a green high-performance concrete pole mixed with recycled aggregates, which is composed of green high-performance concrete mixed with recycled aggregates and a steel skeleton. The green high-performance concrete mixed with recycled aggregates includes 600-850 kg / m of cement in terms of mix ratio. 3 , silica fume 100~200kg / m 3 , fly ash 20~50kg / m 3 , Polyaluminium chloride waste residue 50~250kg / m 3 , Sand 800~1100kg / m 3、Iron tailings 200~500kg / m 3 , carbide slag 10~50kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 8~15kg / m 3 , Fresh water 80~140kg / m 3 , Recycled water 30~60kg / m 3 The polyaluminium chloride waste residue and recycled water are obtained by the following steps:

[0006] S1. Collect the flushing water from the concrete mixing station as wastewater, and conduct preliminary sedimentation of the wastewater in a sedimentation tank to remove large suspended solids and silt;

[0007] S2. Weigh 8-12 kg of polyaluminium chloride solid and dissolve it in 100-120 L of fresh water, stir evenly until it is completely dissolved, add the prepared polyaluminium chloride solution into the wastewater through a metering pump, start the stirring equipment immediately, stir at a speed of 60-100 rpm for 2-5 min to ensure that the polyaluminium chloride solution and the wastewater are fully mixed, and then stir at 20-30 rpm for 10-20 min to promote the formation and growth of flocs;

[0008] S3. The flushing water after flocculation is introduced into the sedimentation tank and allowed to stand for 1 to 2 hours to allow the flocs to settle naturally. After the sedimentation is completed, the supernatant is discharged through the overflow port, and the recycled water is obtained after the test is qualified;

[0009] S4. The obtained flocculent is initially dehydrated by a plate and frame filter press, and then air-washed for 3 to 5 minutes by a washing system, dried, and crushed to obtain polyaluminium chloride waste residue.

[0010] Preferably, the sand is Qingyuan river sand with a fineness modulus of 2.0 to 3.0; the steel fiber is 30 mm end hook type steel fiber; preferably, the silica fume is semi-densified silica fume with a SiO2 content of 96%; the average particle size of the polyaluminium chloride waste residue is 0.08 to 0.30 mm; the average particle size of the iron tailings powder is 0.005 to 0.20 mm; and the average particle size of the carbide slag is 0.01 to 0.20 mm.

[0011] Preferably, the fresh water can be selected from one or more of natural water sources such as mountain spring water or well water, filtered water, mineral water, purified water, and tap water. Preferably, the fresh water comes from tap water.

[0012] A mixing station with an annual production capacity of 500,000 cubic meters will discharge up to 80,000 tons of wastewater each year due to site flushing, sand and gravel conveyor belt cleaning, and production and transportation equipment cleaning. Therefore, the wastewater from the mixing station should be properly disposed of and reused.

[0013] Polyaluminum chloride type flocculants have better flocculation effect in solutions with a pH value below 9. Therefore, when recycling water, the polyaluminum chloride solution is added to the wastewater to play two main roles. The first is to adjust the pH value of the wastewater to below 9, and the second is to adsorb impurities and suspended matter in the wastewater. However, the amount of polyaluminum chloride used cannot be too much, otherwise it will cause the chloride ion content of the recycled water to exceed the standard. Therefore, the preferred amount of the polyaluminum chloride solution added is 1200-1800L of polyaluminum chloride solution per 1,000 tons of wastewater.

[0014] Many impurities in wastewater will affect the performance of concrete, so we need to monitor these items in the recycled water, such as the concentration of chloride ions, sulfate ions, insoluble matter and pH range in the recycled water.

[0015] Preferably, the chloride ion concentration in the monitored recovered water is ≤1000 mg / L, the sulfate ion concentration is ≤200 mg / L, the insoluble matter concentration is ≤2000 mg / L, and the pH range is 4.5 to 8.5.

[0016] More preferably, the chloride ion concentration in the monitored recovered water is ≤800 mg / L, the sulfate ion concentration is ≤150 mg / L, the insoluble matter concentration is ≤1200 mg / L, and the pH range is 5.5 to 8.0.

[0017] More preferably, the chloride ion concentration in the monitored recovered water is ≤700 mg / L, the sulfate ion concentration is ≤80 mg / L, the insoluble matter concentration is ≤900 mg / L, and the pH range is 6.5 to 7.5.

[0018] Preferably, the dehydration pressure of the plate and frame filter press in step S4 is 0.6-1.2 MPa, and the air pressure of the purge system is 0.3-0.8 MPa; the drying is performed using a rotary dryer at a temperature of 180-200°C.

[0019] Preferably, the steel skeleton includes prestressed longitudinal force-bearing steel wires, longitudinal force-bearing steel bars, spiral bars and cold-drawn low-carbon steel wires.

[0020] Preferably, the number of the prestressed longitudinal force-bearing steel wires is 6 to 8, with a diameter of 10 to 13 mm; the number of the longitudinal force-bearing steel bars is 6 to 8, with a diameter of 22 to 28 mm; the diameter of the spiral bars is 4 to 6 mm, and the spiral bar spacing is 50 to 120 mm; the diameter of the cold-drawn low-carbon steel wire is 6 to 8 mm, and the wire spacing is 600 to 800 mm.

[0021] The present invention also protects a method for preparing the green high-performance concrete pole mixed with recycled aggregate, comprising the following steps:

[0022] 1) further grinding and screening the polyaluminium chloride waste residue, iron tailings powder and carbide slag respectively;

[0023] 2) Mixing the polyaluminium chloride waste residue, iron tailings powder and carbide slag evenly according to the mixing ratio, and calcining at 600-800° C. for 1-2 hours to obtain a mixture;

[0024] 3) Mix cement, silica fume, fly ash, sand and the mixture obtained in step 2) according to the mix ratio, stir for 1 to 5 minutes, add water, stir for 2 to 5 minutes, add a water reducer, continue to stir for 2 to 10 minutes, then slowly add steel fiber and continue to stir for 2 to 10 minutes, discharge the material, put the steel skeleton into a mold and cast it, produce it by centrifugal molding process, and cure it by normal pressure steam curing.

[0025] Preferably, in step 2), the ratio of the polyaluminium chloride waste residue to the carbide slag is (10:1) to (3:1).

[0026] Beneficial Effects

[0027] The present invention provides a green high-performance concrete pole mixed with recycled aggregate, which has the following beneficial effects compared with the prior art:

[0028] 1) Through secondary treatment of wastewater from concrete mixing plants, the treated recycled water and polyaluminium chloride waste residue are reused in concrete production, thus achieving the recycling of resources, reducing direct discharge of wastewater and avoiding environmental pollution;

[0029] 2) Using wastewater and waste residue as raw materials for concrete reduces the dependence on fresh water and raw materials in the concrete production process, thereby reducing production costs;

[0030] 3) The wastewater treatment process of the present invention is simple and efficient. Polyaluminium chloride waste residue is obtained through precipitation and flocculation process. The activity of the polyaluminium chloride waste residue is further improved under the action of thermal excitation. At the same time, the carbide slag as waste is decomposed under high temperature to obtain calcium oxide as an alkali metal activator, which can promote the solid phase reaction of SiO2, Al2O3 and CaO in the polyaluminium chloride waste residue, thereby improving the activity of the polyaluminium chloride waste residue. Finally, the carbide slag and the polyaluminium chloride waste residue can be neutralized with each other to avoid excessive acidity and alkalinity of the material.

[0031] 4) Using iron tailings powder to replace part of the river sand not only reduces the proportion of river sand, but also allows the reuse of waste, reduces the amount of landfill, and relieves the pressure of garbage disposal. The activity of iron tailings is further improved under thermal excitation, and the surface is further modified by ion exchange and adsorption of calcium chloride produced by reaction with polyaluminium chloride waste residue and carbide slag.

[0032] The green high-performance electric pole of the present invention not only meets high requirements in performance, but also realizes resource utilization of wastewater and waste residue obtained after treating the wastewater during the production process, which is in line with the concept of green and sustainable development. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0035] The raw materials used in the embodiments and comparative examples are described as follows:

[0036] Polyaluminium chloride: content 28%-30%, item number W00332, purchased from Jiyesheng Chemical;

[0037] Cement: Portland cement, PII 52.5R, produced by Zhujiang Cement Plant;

[0038] Silica fume: semi-densified silica fume, SiO2 content 96%, purchased from Sichuan Ewende, 960U;

[0039] Fly ash: Class II fly ash, Wuhan Lianhekang Biotechnology Co., Ltd.;

[0040] Sand: Qingyuan river sand, fineness modulus 2.0-3.0;

[0041] Iron tailings powder: density is 2.75g / cm 3 , particle size is 0.005~0.5mm, Liaoning Jiahe Pengcheng Powder Technology Co., Ltd.;

[0042] Carbide slag: slag particle size is 1-50mm, Huzhou Kangshan Street Chixiang Building Materials;

[0043] Steel fiber: end hook type steel fiber, SF100 / 60BP, purchased from Bolpais;

[0044] Water reducing agent: polycarboxylic acid water reducing agent, -IV, purchased from Jiangsu Subot;

[0045] Water: Guangzhou tap water, in line with the requirements of the standard "Mixing Water for Concrete" (JGJ 63-2006).

[0046] Wastewater 1 to 5: Flushing water from different batches of concrete mixing plants.

[0047] Prestressed longitudinal force steel wire: diameter 12 mm, grade SWRH72B, purchased from Shagang Steel;

[0048] Longitudinal stress-bearing steel bars: diameter 28 mm, grade HRB500E, purchased from Shagang Steel;

[0049] Spiral ribs: 5 mm in diameter, grade DC01 purchased from Shagang Steel;

[0050] Cold drawn low carbon steel wire: 8 mm in diameter, grade DC01, purchased from Shagang Steel.

[0051] Unless otherwise specified, the components and raw materials used in the preparation examples, embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0052] The recovered water and polyaluminium chloride waste residue in the present invention are prepared by the following steps:

[0053] Recycled water 1:

[0054] The wastewater 1 is initially precipitated in a sedimentation tank to remove large suspended solids and silt;

[0055] Weigh 8kg of solid polyaluminium chloride and dissolve it in 100L of water. Stir evenly until it is completely dissolved. Add the prepared polyaluminium chloride solution into the wastewater through a metering pump at a ratio of 1800L per 1,000 tons of wastewater. Immediately start the stirring equipment and stir at 80rpm for 3min to ensure that the polyaluminium chloride solution and the wastewater are fully mixed. Then stir at 25rpm for 20min to promote the formation and growth of flocs.

[0056] The coagulated wastewater is introduced into the sedimentation tank and allowed to stand for 2 hours to allow the flocs to settle naturally. After the sedimentation is completed, the supernatant is discharged through the overflow port to obtain recycled water, which is then monitored.

[0057] Recycled water 2:

[0058] Compared with the recycled water 1, the difference is that the sedimentation tank performs preliminary sedimentation on the wastewater 2, 12kg of solid polyaluminium chloride is weighed and dissolved in 120L of water, and added into the wastewater through a metering pump at a ratio of 1200L per 1,000 tons of wastewater.

[0059] Recycled water 3:

[0060] Compared with the recycled water 1, the difference is that the wastewater 1 is replaced by the wastewater 3.

[0061] Recycled water 4:

[0062] Compared with the recycled water 1, the difference is that the wastewater 4 is initially precipitated in the sedimentation tank and added into the wastewater through a metering pump at a ratio of 2200L per thousand tons of wastewater.

[0063] Recycled water 5:

[0064] Compared with the recycled water 1, the difference is that the wastewater 5 is initially precipitated in the sedimentation tank and added into the wastewater through a metering pump at a ratio of 1000L per 1,000 tons of wastewater.

[0065] Polyaluminium chloride waste residue 1:

[0066] The flocculants in the recovered water 1 are passed through a plate and frame filter press for preliminary dehydration at a pressure of 0.8 MPa, and then are blown through a blowing system with air at a pressure of 0.5 MPa for 5 minutes, broken, and then dried in a rotary dryer at a temperature of 150°C to obtain polyaluminium chloride waste residue.

[0067] Polyaluminium chloride waste residue 2:

[0068] Compared with the polyaluminium chloride waste residue 1, the difference is that the polyaluminium chloride waste residue comes from the flocculants in the recycled water 2.

[0069] Polyaluminium chloride waste residue 3:

[0070] Compared with the polyaluminium chloride waste residue 1 , the difference is that the polyaluminium chloride waste residue comes from the flocculants in the recycled water 3 .

[0071] Steel skeleton:

[0072] Six prestressed longitudinal force-bearing steel wires are used, and eight longitudinal force-bearing steel bars are used as the main reinforcement; cold-drawn low-carbon steel wires are used as the frame rings with a spacing of 600mm; spiral reinforcements are used as annular structures, with a spacing of 50mm within 1.5m from both ends of the pole, and a spacing of 100mm in the remaining sections.

[0073] The following is the test method of the performance parameters involved in the present invention:

[0074] (1) Chloride ion concentration: Tested in accordance with the relevant requirements of the national standard "Water quality-Determination of chloride-Silver nitrate titration method" GB / T 11896;

[0075] (2) Sulfate ion Concentration: Tested in accordance with the relevant requirements of the national standard "Water quality-Determination of sulfate-Gravimetric method" GB / T11899;

[0076] (3) Insoluble matter concentration: Tested in accordance with the relevant requirements of the national standard "Water quality - Determination of suspended matter - Gravimetric method" GB / T 11901;

[0077] (4) pH value: Tested in accordance with the relevant requirements of the national standard "Water quality - Determination of pH value by glass electrode method" GB / T 6920;

[0078] (5) Compressive strength: The specimen size is 150 mm × 150 mm × 150 mm, and the test is carried out in accordance with the relevant provisions of GB / T 50081-2019;

[0079] (6) Vertex deflection: The cantilever test is carried out in accordance with the relevant provisions of the standard "Ring Concrete Poles" GB 4623-2014.

[0080] Table 1 Concrete water testing data

[0081]

[0082] Examples 1 to 11

[0083] A green high-performance concrete pole mixed with recycled aggregate, the preparation method comprising the following steps:

[0084] 1) further grinding the polyaluminium chloride waste residue, iron tailing powder and carbide slag respectively, and the average particle size of the polyaluminium chloride waste residue after screening is 0.15mm, the average particle size of the iron tailing powder is 0.10mm, and the average particle size of the carbide slag is 0.15mm;

[0085] 2) mixing the polyaluminium chloride waste residue, iron tailings powder and carbide slag evenly according to the mixing ratio, and calcining at 700° C. for 2 h to obtain a mixture;

[0086] 2) Mix cement, silica fume, fly ash, sand and the mixture obtained in step 2) according to the mix ratio, stir for 5 minutes, add fresh water and recycled water, stir for 5 minutes, add water reducer, continue stirring for 8 minutes, slowly add steel fiber and continue stirring for 6 minutes, and discharge. According to the relevant provisions of "Ring Concrete Pole" GB4623-2014, the same steel skeleton is used, and the C120 high-performance green concrete pole with a designed cracking test bending moment of 97.5kN·m is used. The wall thickness is 50mm, the shape is a tapered pole, the taper is 1 / 75, the tip diameter is 190mm, the root diameter is 350mm, the pole length is 12m, and it is produced by centrifugal molding process and cured by normal pressure steam curing for 27 days.

[0087] Example 12

[0088] Compared with the preparation method of Example 1, the difference is that in step 1), the average particle size of the polyaluminium chloride waste residue after screening is 0.50 mm, the average particle size of the iron tailings powder is 0.40 mm, and the average particle size of the carbide slag is 0.40 mm;

[0089] Table 2 Green high performance concrete formula (Examples 1 to 13, in terms of mix ratio kg / m 3)

[0090]

[0091]

[0092] Comparative Example 1

[0093] Compared with the preparation method of Example 1, the difference is that in step 2), the polyaluminium chloride waste residue is mixed with iron tailing powder and carbide slag according to the mixing ratio without calcining to obtain a mixture.

[0094] Comparative Example 2

[0095] Compared with the preparation method of Example 1, the difference is that in step 2), the calcination temperature is 400°C.

[0096] Comparative Example 3

[0097] Compared with the preparation method of Example 1, the difference is that in step 2), the calcination temperature is 900°C.

[0098] Comparative Example 4

[0099] Compared with the preparation method of Example 1, the difference is that in step 2), the polyaluminium chloride waste residue, iron tailings powder and carbide slag are calcined separately at 700° C. for 2 h without mixing.

[0100] Comparative Examples 5 to 8

[0101] The preparation method is the same as that of Example 1.

[0102] Table 3 Comparative Examples 1 to 8 formulations (in terms of mix ratio kg / m 3 )

[0103]

[0104]

[0105] Table 4 Performance test results of embodiments and comparative examples

[0106]

[0107]

[0108] It can be seen from the data of the embodiments and comparative examples that appropriate addition of the polyaluminium chloride waste slag, carbide slag, iron tailings powder and recycled water prepared by the present invention can, on the one hand, effectively reduce the discharge of waste, and on the other hand, the concrete prepared therefrom has excellent performance, and the performance meets the compressive strength ≥ 120MPa, meeting the standards of most countries regarding the minimum compressive strength of C120 concrete greater than 120MPa, and the properties of the poles prepared from the concrete are also very excellent.

[0109] It can be seen from the data in Table 1 that adding too much polyaluminium chloride solution will lead to an increase in the chloride ion content in the recovered water and the pH of the solution is too low; when too little polyaluminium chloride solution is added, the polyaluminium chloride added in the early stage fails to effectively flocculate impurities in the water due to the high pH, ​​and only a small part of the polyaluminium chloride plays a flocculation role after the pH is lowered.

[0110] It can be seen from the data in Table 4 that the concrete poles prepared from the obtained concrete have excellent properties. The higher the compressive strength of the concrete, the smaller the vertex deflection of the prepared concrete poles. This shows that the high-performance concrete enhances the bending stiffness of the poles and effectively prevents cracks in the concrete. It can be seen from the data of Examples 3 to 7 in Table 4 that with the increase in the proportion of polyaluminium chloride waste slag and carbide slag, the compressive strength of the prepared concrete first increases and then decreases; it can be seen from the data of Examples 5, 8 to 11 that the performance of the concrete prepared using the preferred recycled water is better; it can be seen from the data of Examples 5 and 12 that when the average particle size of polyaluminium chloride waste slag, iron tailings powder, and carbide slag is smaller, the performance of the prepared concrete is better; it can be seen from the data of Comparative Examples 1 to 3 that the activity of the waste that is not calcined or the calcination temperature is too low or too high is low, resulting in poor performance of the concrete; it can be seen from the data of Comparative Example 4 that when polyaluminium chloride waste slag, iron tailings powder, and carbide slag are added, the performance of the concrete is better. When the polyaluminium chloride waste slag and carbide slag are calcined separately, the compressive strength of the concrete is greatly reduced; it can be seen from the data of Examples 5, 8, and 9 that the performance of the concrete prepared by obtaining polyaluminium chloride waste slag from different batches of wastewater is slightly different, which shows that the performance of the obtained polyaluminium chloride waste slag has good consistency; it can be seen from the data of Comparative Example 5 that adding appropriate amounts of polyaluminium chloride waste slag and carbide slag can enhance the strength of concrete; it can be seen from the data of Comparative Examples 6 to 7 that adding appropriate amounts of iron tailings powder as fine aggregate can increase the strength of concrete, thereby improving the performance of concrete poles; it can be seen from the data of Comparative Example 8 that not adding carbide slag to treat the polyaluminium chloride waste slag will lead to a decrease in the strength of the concrete.

[0111] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A green high-performance concrete pole mixed with recycled aggregate, characterized in that: The green high-performance concrete mixed with recycled aggregate and a steel skeleton are composed of the green high-performance concrete mixed with recycled aggregate, wherein the green high-performance concrete mixed with recycled aggregate includes 600-850 kg / m of cement according to the mix ratio. 3 Silica fume 100~200 kg / m 3 、Fly ash 20~50 kg / m 3 、Polyaluminium chloride waste residue 50~250 kg / m 3 , sand 800~1100 kg / m 3 , Iron tailings powder 200~500 kg / m 3 , carbide slag 10~50 kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 8~15 kg / m 3 、Fresh water 80~140 kg / m 3 , Recycled water 30~60 kg / m 3 The polyaluminium chloride waste residue and recycled water are obtained by the following steps: S1. Collect the flushing water from the concrete mixing station as wastewater, and conduct preliminary sedimentation of the wastewater through a sedimentation tank to remove large suspended solids and silt; S2. Weigh 8-12 kg of polyaluminium chloride solid and dissolve it in 100-120 L of fresh water. Stir evenly until it is completely dissolved. Add the prepared polyaluminium chloride solution into the wastewater through a metering pump. Immediately start the stirring equipment. Stir at a speed of 60-100 rpm for 2-5 min to ensure that the polyaluminium chloride solution and the wastewater are fully mixed. Then stir at 20-30 rpm for 10-20 min to promote the formation and growth of flocs. S3. The flushing water after flocculation is introduced into the sedimentation tank and allowed to stand for 1 to 2 hours to allow the flocs to settle naturally. After the sedimentation is completed, the supernatant is discharged through the overflow port, and the recycled water is obtained after the test is qualified; S4. The obtained flocculent is passed through a plate and frame filter press for preliminary dehydration, and then purged with air through a purge system for 3 to 5 minutes, dried, and crushed to obtain polyaluminium chloride waste residue; In the method for preparing the concrete pole, the polyaluminium chloride waste residue, iron tailings powder and carbide slag are used in the following manner: 1) further grinding and screening the polyaluminium chloride waste residue, iron tailings powder and carbide slag respectively; 2) Evenly mix the polyaluminium chloride waste residue, iron tailings powder and carbide slag according to the mixing ratio, and calcine at 600-800°C for 1-2 h to obtain a mixture.

2. The concrete pole according to claim 1, characterized in that: The amount of polyaluminium chloride solution added in step S2 is 1200-1800 L of polyaluminium chloride solution per 1,000 tons of wastewater.

3. The concrete pole according to claim 1, characterized in that: The qualified detection standard of the recycled water is that the chloride ion concentration is ≤1000 mg / L, the sulfate ion concentration is ≤300 mg / L, the insoluble matter concentration is ≤2000 mg / L, and the pH range is 4.5~8.

5.

4. The concrete pole according to claim 1, characterized in that: The average particle size of the polyaluminium chloride waste residue is 0.08-0.30 mm; the average particle size of the iron tailings powder is 0.005-0.20 mm; and the average particle size of the carbide slag is 0.01-0.20 mm.

5. The concrete pole according to claim 1, characterized in that: In step S4, the dehydration pressure of the plate and frame filter press is 0.6-1.2 Mpa, the air pressure of the purge system is 0.3-0.8 Mpa, and the drying is performed using a rotary dryer at a temperature of 180-200°C.

6. The method for preparing a concrete pole according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) further grinding and screening the polyaluminium chloride waste residue, iron tailings powder and carbide slag respectively; 2) Mixing the polyaluminium chloride waste residue, iron tailings powder and carbide slag evenly according to the mixing ratio, calcining at 600-800°C for 1-2 hours to obtain a mixture; 3) Mix cement, silica fume, fly ash, sand and the mixture obtained in step 2) according to the mix ratio, stir for 1-5 min, add fresh water and recycled water, stir for 2-5 min, add water reducer, continue to stir for 2-10 min, then slowly add steel fiber and continue to stir for 2-10 min, discharge, put the steel skeleton into the mold and cast, produce by centrifugal molding process, and cure by normal pressure steam curing.

7. The method for preparing a concrete pole according to claim 6, characterized in that: In step 2), the mixing ratio of polyaluminium chloride waste slag to carbide slag is (10:1) to (3:1).